2017
DOI: 10.3892/or.2017.5587
|View full text |Cite
|
Sign up to set email alerts
|

Migration of oral squamous cell carcinoma cells are induced by HGF/c-Met signalling via lamellipodia and filopodia formation

Abstract: Abstract. The activation of receptor tyrosine kinases (RTKs) results in cellular effects including cell proliferation, survival, migration and invasion; RTKs also play an important role in tumourigenesis. It has been reported that EGFR signalling controls the migration of oral squamous cell carcinoma (OSCC) SAS and HSC3 cells but not of HSC4 cells, although the proliferation of HSC4 cells is regulated by EGF/EGFR. In the present study, we investigated the roles of EGFR and the c-Met signalling pathway in cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…EGFR and MET inhibitors induced changes in actin cytoskeleton organization of oral squamous cell carcinoma cells. Furthermore, MET inhibitor reduced filopodia and lamellipodia formation, thus decreasing migration of these cells . Miekus et al also observed in MET‐deficient cervical carcinoma cells, that F‐actin was located under the cell membrane and did not form regular stress fibres which were present in control cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…EGFR and MET inhibitors induced changes in actin cytoskeleton organization of oral squamous cell carcinoma cells. Furthermore, MET inhibitor reduced filopodia and lamellipodia formation, thus decreasing migration of these cells . Miekus et al also observed in MET‐deficient cervical carcinoma cells, that F‐actin was located under the cell membrane and did not form regular stress fibres which were present in control cells.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, MET inhibitor reduced filopodia and lamellipodia formation, thus decreasing migration of these cells. 43 Miekus et al 44 and MMP-9-mediated degradation of E-cadherin. 49 Therefore, we also analysed proteolytic activity of generated variants of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In OSCC, c-MET has been shown to be upregulated in OSCC tissues, and its expression was associated with tumor stage (31). In addition, downregulating of c-MET could inhibit OSCC cell proliferation and invasion (32). Thus, in our study, we selected c-MET as a direct target of miR-152, and found that overexpression miR-152 significantly inhibited c-MET and the downstream signaling pathway, c-MET expression was upregulated in OSCC tissues, and inversely correlated with miR-152 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The HSC-4 and Ca9-22 human OSCC cell line was used as an experimental model in this study. HSC-4 and Ca9-22 cells are negative for cancer stemness (41) and responsive to HGF and c-Met inhibitor SU11274 (23). Thus, the effects of curcumin on HGF-induced EMT and the invasive and migratory potential of HSC-4 and Ca9-22 cells were investigated.…”
Section: Discussionmentioning
confidence: 99%